Lithium silicate based membranes for high temperature CO2 separation - Yamaguchi, T.; Niitsuma, T.; Nair, Balagopal; Nakagawa, K. (Elsevier B.V, 2007)
Processing and characterisation of a novel membrane system for CO2 separation is detailed. The membrane was made of Lithium Orthosilicate (Li4SiO4), which has potential to react with CO2 molecules reversibly at high temperature. Using the membrane, a separation factor of 5.5 was measured between CO2 and N2 gas molecules at a temperature of 525C. The gas permeance value through the membrane at 525C was around 10-8 mol/m2 s Pa. Ionic diffusion through the liquid phase electrolyte and solid phase skeleton, produced by the reaction between CO2 and Li4SiO4,was suggested to assist the selective permeance of CO2. This facilitation effect was experimentally identified by examining the variation in CO2 flux with partial pressure. Oxygen ion conductivity through the skeleton material, Li2SiO3, is reportedly very high and therefore charge balance should have been achieved by O2- transfer through the skeleton.